Picenum and the Ager Gallicus at the Dawn of the Roman Conquest - Boschi, Federica (Archaeopress, 2020)
Intro -- A_IndexCaptions_01_Open -- B_Prelims_02_Open -- Chapter_01_Open -- Chapter_02_Open -- Chapter_03_Open -- Chapter_04_Open -- Chapter_05_Open -- Chapter_06_Open -- Chapter_07_Open -- Chapter_08_Open -- Chapter_09_Open -- Chapter_10_Open -- X. A crossroads in the central Potenza Valley: -- non-invasive research into settlement (dis-)continuity at Monte Franco -- (Pollenza, Marche, Italy) -- Introduction -- Current research at Monte Franco (Pollenza) -- Results -- The necropolis of Moie di Pollenza -- Site 12 / 85 -- Functional areas and spatial organization beyond Site 12 -- The longue durée of Site 77 -- Evidence for land management and controlled hydrology -- Discussion: settlement and land use (dis-)continuity at Monte Franco -- Conclusion -- Chapter_11_Open -- Chapter_12_Open -- Chapter_13_Open -- XIII. The Urban Archaeology Project in Asculum. From civitas caput gentis to civitas foederata -- Federica Boschi, Enrico Giorgi, University of Bologna -- Tommaso Casci Ceccacci, Filippo Demma, Soprintendenza Archeologia Belle Arti e Paesaggio delle Marche -- Chapter_14_Open -- Chapter_15_Open -- Chapter_16_BibliographyOpen -- Dall'Aglio, P.L. and P. Campagnoli (eds) 2002. Sulle tracce del passato. Percorsi archeologici nella provincia di Pesaro e Urbino. Urbania: Arti Grafiche Stibu. -- Dall'Aglio, P.L., S. De Maria and A. Mariotti (eds) 1991. Archeologia delle valli marchigiane Misa, Nevola e Cesano. Perugia: Electa Editori Umbri. -- Dall'Aglio, P.L. and I. Di Cocco (eds) 2004. Pesaro romana: archeologia e urbanistica. Bologna: Ante Quem. -- Dall'Aglio, P.L., C. Franceschelli and C. Tassinari 2014. Prima considerazioni sulla città romana di Ostra alla luce dei nuovi scavi, in Baldelli and Lo Schiavo 2014: 829-848.